2019
DOI: 10.1097/01.hjh.0000571936.90615.ec
|View full text |Cite
|
Sign up to set email alerts
|

Selected Matrix Metalloproteinases Activity and Hypertension-Mediated Organ Damage in Relation to Uric Acid Serum Level

Abstract: Background: Atherosclerosis is as a systemic inflammatory disease associated with the activation of many mediators, including matrix metalloproteinases (MMPs), and may be amplified by abnormal high serum uric acid (UA) concentration (hyperuricemia, HU). The aim of the study was to determine the relationship between serum UA concentration and activity of MMPs and their correlation with the hypertension-mediated organ damage (HMOD) intensity. Methods: One hundred and nine patients untreated with antihypertensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…Higher serum UA concentrations were found to be associated with higher mean arterial pressure and hypertension [ 39 ] as well as with an increased risk of type 2 diabetes [ 40 ]. A possible positive relation of serum uric acid to MMPs [ 41 , 42 ] as well as negative correlation between SOD and uric acid were documented. It has been found that decreased levels of antioxidants such as SOD in plasma and tissues are associated with increased UA levels in blood circulation [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher serum UA concentrations were found to be associated with higher mean arterial pressure and hypertension [ 39 ] as well as with an increased risk of type 2 diabetes [ 40 ]. A possible positive relation of serum uric acid to MMPs [ 41 , 42 ] as well as negative correlation between SOD and uric acid were documented. It has been found that decreased levels of antioxidants such as SOD in plasma and tissues are associated with increased UA levels in blood circulation [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in patients with CA, serum MMP-3 protein levels were increased in those with vulnerable plaques, and were positively correlated with a 2-year occurrence of cerebrovascular events [ 73 ]. A correlation between MMP-3 activity and CIMT was found in untreated subjects with arterial hypertension [ 74 ]. In the general population, active and total MMP-3 demonstrated a relationship with the carotid plaque score [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gruszka, et al encontraron una asociación fuerte entre los niveles séricos de ácido úrico y la actividad de la enzima matriz metaloproteinasa 3, la cual tiene un papel fundamental en la activación de otras metaloproteasas. El resultado final es la remodelación vascular y formación de placas de ateroma 15 . Es interesante señalar que Tsai, et al reportaron que la asociación entre ácido úrico y VOP no es secundaria a un aumento del proceso inflamatorio 16 .…”
Section: Discussionunclassified